Kedudukan Tanah Kas Desa Setelah Berlakunya Peraturan Gubernur Istimewa Yogyakarta Nomor 34 Tahun 2017 tentang Pemanfaatan Tanah Desa (Studi di Kelurahan Argomulyo, Kapanewon Cangkringan, Kabupaten Sleman) - Amanda Nurdiana Puspitasari; Mukmin Zakie (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research is motivated by the legal dualism that applies in the Special Region of Yogyakarta regarding village treasury land, namely national land law and special regulations. The aim of this research is to determine the position of village treasury land in Argomulyo Village. Kapanewon Cangkringan, Sleman Regency after the enactment of Regulation of the Governor of the Special Region of Yogyakarta Number 34 of 2017 concerning Village Land Utilization and the process of adjusting the certificate of use rights on land belonging to the Sultanate. This research uses empirical research methods, namely research that looks at law in real terms and how the law works. The approach method used is the historical juridical approach. The results of this research are that the position of village treasury land in Argomulyo Village, Kapanewon Cangkringan, Sleman Regency after the enactment of Yogyakarta Special Region Governor Regulation Number 34 of 2017 is still on state land based on the provisions of national land law. This is because the position of village treasury land has not yet been restored as land belonging to the Sultanate in accordance with its origins, so this regulation has not been implemented in its entirety. The process of adjusting the position is carried out by adjusting the certificate of use rights to be on land belonging to the Sultanate based on the verification report which states that the land object is the right of the anggaduh by affixing a note in the certificate recording column.